2015
DOI: 10.1007/s00453-015-0069-8
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing Phylogenetic Level-1 Networks from Nondense Binet and Trinet Sets

Abstract: Binets and trinets are phylogenetic networks with two and three leaves, respectively. Here we consider the problem of deciding if there exists a binary level-1 phylogenetic network displaying a given set T of binary binets or trinets over a taxon set X , and constructing such a network whenever it exists. We show that this is NP-hard for trinets but polynomial-time solvable for binets. Moreover, we show that the problem is still polynomial-time solvable for inputs consisting of binets and trinets as long as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…The closest works to our proposed method here are those of Huber et al (2017); Hejase et al (2018). In (Huber et al, 2017), the authors devised an algorithm that is restricted to combining binet and trinet topologies (no divergence times) into level-1 networks (A phylogenetic network is level-1 if no two cycles in its underlying undirected graphs share a node). The work of Hejase et al (2018) proposed another divide-and-conquer method to infer subnetworks and combine them.…”
Section: Introductionmentioning
confidence: 99%
“…The closest works to our proposed method here are those of Huber et al (2017); Hejase et al (2018). In (Huber et al, 2017), the authors devised an algorithm that is restricted to combining binet and trinet topologies (no divergence times) into level-1 networks (A phylogenetic network is level-1 if no two cycles in its underlying undirected graphs share a node). The work of Hejase et al (2018) proposed another divide-and-conquer method to infer subnetworks and combine them.…”
Section: Introductionmentioning
confidence: 99%
“…, τ 12 on X = {x, y, z} from [7] that are also level-1 networks in our sense. In the same paper it was observed that even the slightly more general 1-nested networks are uniquely determined by their induced trinet sets (see also [8] for more on constructing level-1 networks from trinets, and [14] for an extension of this result to other classes of phylogenetic networks).…”
Section: δ-Triplets δ-Tricycles and δ-Forksmentioning
confidence: 93%
“…2015 for a related algorithm). In particular, a sink set of  can be found in polynomial time by computing the strongly connected components of  (Tarjan 1972) and checking for each of them whether it is a sink set.…”
Section: Complexity Of Binet Compatibilitymentioning
confidence: 99%